Measuring spatiotemporal dynamics of cyclic AMP signaling in real-time using FRET-based biosensors. - Gesellchen, F; Stangherlin, A; Surdo, N; Terrin, A; Zoccarato, A; Zaccolo, M (2011)
Cyclic AMP governs many fundamental signaling events in eukaryotic cells. Although cAMP signaling has been a major research focus for a long time, recent technological developments are revealing novel aspects of this paradigmatic pathway. In this chapter, we give an overview over current fluorescence resonance energy transfer (FRET)-based sensors for detection of cAMP dynamics, and their application in monitoring local, compartmentalized cAMP signals within living cells. A basic step-by-step protocol is given for conducting a FRET experiment in primary cells with a unimolecular cAMP sensor, which can easily be adapted to a user's specific requirements.